X. Study on the Influence Mechanism of Digital Economy Development on China’s Service Trade Exports-Based on Countries Along the “Belt and Road” - Yin, Baomin; Li, Guopeng (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
The digital economy has injected a strong impetus into developing service trade along the "Belt and Road" between China and other countries. Based on the countries along the "Belt and Road", this paper analyses the impact mechanism of the digital economy on China's service trade exports, focusing on cost reduction and market expansion, and puts forward corresponding policy recommendations.